S4D:4 Variant of the tnfsf13b gene encoding for b-cell activating factor confers susceptibility to sle, increased serum baff cytokine and autoantibodies production. (21st March 2018) - Piga, M; Steri, M; Orrù, V; Idda, L; Pitzalis, M; Cucca, F; Mathieu, A
Abstract : Background: Recently, a variant in TNFSF13B, encoding the cytokine and drug target B-cell activating factor (BAFF), has been associated with Systemic Lupus Erythematosus (SLE). 1 The aim of this study was to explore the BAFF-var effect on serologic and clinical features in a cohort of patients affected with SLE. Methods: Overall, 190 Sardinian patients affected with SLE according to the modified 1997 ACR classification criteria and 256 Sardinian healthy controls were enrolled in this study and genotyped for the BAFF-var. In each patient demographic, serologic and clinical characteristics retrospectively collected at the time of SLE diagnosis and pre-therapy were recorded. Sera from 76 SLE patients, collected before starting therapy and stored at −80°, and 79 controls were used to measure soluble BAFF cytokine (ELISA). Results: BAFF-var allelic frequency was higher in SLE patients (0.368) than in healthy controls (0.259) and associated with a higher risk of developing SLE (OR: 1.6; 95% CI: 1.2 to 2.2; p=0.0005). Serum BAFF concentration was significantly increased (p=1.61×10–9) in SLE cases (mean 1530 pg/ml; range 328–9327 pg/ml) versus healthy controls (mean 829 pg/ml; range 527–1410 pg/ml). Notably, when we stratified the data according to BAFF-var, the levels of serum BAFF increased in a genotype dependent way (p=0.001). No association with gender or age at SLE onset and BAFF-var was identified. Stratifying SLE manifestations according to ACR classification criteria, no significant correlation with any of the tested manifestations and the BAFF-var genotype was discovered. However, the quantitative levels of anti-dsDNA autoantibodies increased in a BAFF-var genotype dependent way (p=0.004), being higher in patients with BAFF-var homozygosis (88.5 UI/dl, IQR 4.1–491) than in those with wild-BAFF/BAFF-var heterozygosis (48.5 UI/dl, IQR 9.7–197) and wild BAFF homozygosis (29.0 UI/dl, IQR 3.5–116). Conclusion: BAFF-var is associated with higher risk of SLE in general population and it is associated with increased serum BAFF and anti-dsDNA levels suggesting that it could also impact on SLE phenotype and outcomes. Reference: . Steri M, et al. Overexpression of the cytokine BAFF and autoimmunity risk. N Engl J Med2017;376(17):1615–1626.